Fraudulent Financial Reporting Analysis Using Fraud Hexagon Theory in ASEAN Healthcare Sector Companies: Study of healthcare sector companies listed on stock exchanges in ASEAN countries, 2022–2023 - Ririh Anggraini Setyahety; Liliek Nur Sulistiyowati; Dhea Aliza Putri (Institut Teknologi dan Bisnis Asia Malang, 2026)
This research aims to analyze the factors influencing fraudulent financial reporting (FFR) in healthcare sector companies in ASEAN using the Fraud Hexagon Theory. The sample consists of 166 healthcare companies listed on stock exchanges in Indonesia, Malaysia, Thailand, Singapore, and the Philippines for the period 2022–2023. Data were analyzed using IBM SPSS 25. The results show that financial stability and company existence have a negative and significant effect on FFR, while ineffective monitoring and auditor change have a positive and significant effect. Meanwhile, financial targets, external pressure, director change, and project with government have no significant effect. Simultaneously, all variables in the Fraud Hexagon Theory significantly influence FFR. These findings imply that companies with effective supervision and consistent stability are less likely to engage in fraudulent reporting. The research is limited to the healthcare sector during 2022–2023 and may not generalize to other industries or periods.